Educação Ambiental no ensino de Ciências: uma análise dos livros didáticos - LIMA, Adriel Macedo (2022)
Teaching Science with a focus on Environmental Education makes it possible to resize the roles of students and teachers in the classroom, as both begin to assume co-responsibilities in the teaching-learning process, involving a dialogic relationship in which both learn. For this, textbooks, the main resource used in classes, need to propose activities focused on socio-environmental themes. In this sense, this work aims to analyze the approach given to Environmental Education in the activities proposed in Science textbooks for the final years of elementary school. The research developed is qualitative and bibliographical, as it analyzed a collection of textbooks used by Science teachers in the final years of elementary school in the Curuçá-PA school system. The selected activities were analyzed using the Content Analysis method and pointed out that the investigated works propose activities that bring up current socio-environmental themes and focus on the methodological trend of Science, Technology, Society and Environment.